2016
DOI: 10.1186/s13005-016-0127-8
|View full text |Cite
|
Sign up to set email alerts
|

Classification and characterization of class III malocclusion in Chinese individuals

Abstract: BackgroundClass III malocclusion is a maxillofacial disorder that is characterised by a concave profile and can be attributed to both genetic inheritance and environmental factors. It is a clinical challenge due to our limited understanding of its aetiology. Revealing its prototypical diversity will contribute to our sequential exploration of the underlying aetiological information. The objective of this study was to characterize phenotypic variations of Class III malocclusion via a lateral cephalometric analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
33
3
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 35 publications
11
33
3
3
Order By: Relevance
“…As described in previously published studies 5,8,17 , the first three axes represented more than half [58.5%] of the total variation found in the sample, essentially referring to the description of sagittal and vertical parameters, while others 5,8,17 also represented the position of the lower incisor in the first half of the variation derived from the involvement of dental variables in the formation of PCs. Most of the parameters that represent sagittal and vertical measurements in our PC1 (26.6% of variation), PC2 (19.6% of variation), and PC3 (12.3% of variation) are equivalent to the parameters of PC1 (23.7% and 20.6%) and PC2 (17.3% and 19.34%) in other studies 5,8 , while PC1 in another study 17 is more like PC4 (9.3%) and PC5 (6.5%) (ANB, facial angle, and Pg-N perp) in the present research, despite the fact that the same sagittal and vertical parameters were included in these aforementioned components. The observed differences might be at least partially explained by the type of class III patients included and their distribution, essentially based on distinct ethnic origin and growing stage of the included subjects.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…As described in previously published studies 5,8,17 , the first three axes represented more than half [58.5%] of the total variation found in the sample, essentially referring to the description of sagittal and vertical parameters, while others 5,8,17 also represented the position of the lower incisor in the first half of the variation derived from the involvement of dental variables in the formation of PCs. Most of the parameters that represent sagittal and vertical measurements in our PC1 (26.6% of variation), PC2 (19.6% of variation), and PC3 (12.3% of variation) are equivalent to the parameters of PC1 (23.7% and 20.6%) and PC2 (17.3% and 19.34%) in other studies 5,8 , while PC1 in another study 17 is more like PC4 (9.3%) and PC5 (6.5%) (ANB, facial angle, and Pg-N perp) in the present research, despite the fact that the same sagittal and vertical parameters were included in these aforementioned components. The observed differences might be at least partially explained by the type of class III patients included and their distribution, essentially based on distinct ethnic origin and growing stage of the included subjects.…”
Section: Discussionmentioning
confidence: 93%
“…Class III malocclusion has been commonly described as having a retruded or hypoplastic upper maxilla, a prognathic or hyperplastic mandible, or a combination of both 1 . These shared characteristics in skeletal class III malocclusion vaguely define the different sub-phenotypes clearly identified in recent studies [2][3][4][5][6][7][8] .…”
Section: Sub-clustering In Skeletal Class III Malocclusion Phenotypesmentioning
confidence: 99%
“…Few studies indicate the total number of each gender in the different subgroups identified. Nevertheless, differences in gender within clusters can be observed in other studies; for instance, in Li et al [ 34 ], two of the four characterized clusters were disproportionately made up of females (67.4% and 75%).…”
Section: Discussionmentioning
confidence: 64%
“…Cluster analysis for the phenotypic classification of skeletal Class III malocclusion is being increasingly used to establish specific sub-phenotypes within the large variations of this malocclusion [ 23 , 24 , 25 , 26 , 27 , 34 , 40 , 41 ]. The establishment of appropriate, specific, distinguishable, and easy-to-use clinical sub-phenotypes would facilitate future studies focused on treatment outcomes, relapse prognosis, or even diagnostic characterization of this particular malocclusion, which may ultimately lead to more appropriate therapeutic protocols for each sub-phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation